Vibration Control of Linear Split Stirling Cryogenic Cooler for Airborne Infrared Application - A.M. Veprik; V.I. Babitsky; N. Pundak; S.V. Riabzev (Shock and Vibration)
Modern infrared imagers often rely on the split Stirling cryogenic coolers the linear compressors of which are the well-known sources of harmonic disturbance. The traditional method of their passive isolation fails to meet the restraints on the static and dynamic deflections which are originated by the combined action of the airborne g-loading and harsh random vibration.